Tropical cyclone exposure is associated with increased hospitalization rates in older adults - Robbie M. Parks; G. Brooke Anderson; Rachel C. Nethery; Ana Navas-Acien; Francesca Dominici; Marianthi-Anna Kioumourtzoglou (Nature Communications, 2021)
Tropical cyclones can cause severe damage and can thus have devastating impacts on societies. Here, the authors use Medicare data to show that tropical cyclone exposure in the United States is associated with increased hospitalization rates for older adults from many different acute causes.